Les Monuments funéraires et l'histoire du Sultanat de Pasai à Sumatra - Meij, Dick van der (Studia Islamika, 2010)
Book review: Claude Guillot & Ludvik Kalus, Les Monuments funeraires et l'histoire du Sultanat de Pasai a Sumatra, Avec une contribution de Marie-Odette Scalliet. Paris: Cahier d'Archipel 37, 2008, ISBN 978-2-910513-53-5/ISSN 0244-5301, 402 pp.The book gives an exhaustive typology of the various forms of the gravestones and their variations and uses clear photographs to illustrate the various types. Six types have been identified of which one, the ogival style was imported into the area from Cambay, Gujarat, India. The six types are ogival, accolade, accolade with wings, decorated with spirals, pyramidal, and others, all with subdivisions. The book continues with the languages used in the inscriptions on the stones. Although at the time Malay already functioned as the lingua franca in the area, the language used on the stones is predominantly Arabic. The various texts used in the inscriptions are subsequently divided into epitaphs, containing the name of the deceased often elaborated with extensive soubriquets. The epithets for males and females are usually the same but for women a more extensive number of labels is used such as 'the chaste', 'the virtuous', 'the pure' and so on. In addition, genealogies, eulogies, and dates of death and interment are provided.DOI: 10.15408/sdi.v17i1.471